Fertility/longevity trade offs under limiting-male conditions in mating populations of Caenorhabditis elegans - Wu, Deqing (2012)
Evolutionary theories of aging suggest that trade-offs between longevity and fitness should be found under certain conditions. In C. elegans, there is little evidence for the existence of such tradeoffs. We asked if fertility/longevity trade-offs exist in populations of randomly mating males and hermaphrodites. We set up a large population of young males and 5-day-old hermaphrodites that were no longer self-fertile. We then allowed them to mate for one day with an equal number young males and then separated hermaphrodites to individual plates and determined daily fertility of individual hermaphrodites. There was a significant negative relationship between late-life fertility and individual longevity.